Combining Functional Prototyping of 3D Printed Reactors with a Modular Reactor Setup for Continuous Emulsion Polymerization. Issue 8 (26th April 2022) - Zentel, Kristina M.; Reinbeck, Andreas; Deckert, Christian; Pauer, Werner; Luinstra, Gerrit A.
Abstract: The potential for fast and specific process optimization by functional prototyping with 3D printed reactors was shown for a known continuous emulsion polymerization in a modular setup. Three tubular reactors, two with static mixing elements and a continuously stirred tank reactor (CSTR) were printed from polylactic acid. Thermal imaging of the reactors allows to map the basically adiabatic progress of the redox‐started radical polymerization in a space‐resolved way. The application of static mixing elements led to a higher conversion stability and a more uniform product, as expected for a better mass transfer. Polymerization in combinations of CSTR and a tubular reactor showed further improvements of process stability and product uniformity in terms of particle size and mol masses. Abstract : Four reactors with different mixing characteristics were designed, 3D printed and applied individually as well as in modular combinations for the continuous emulsion polymerization of styrene/butyl acrylate.